Exploring the Susceptibility of Turbid Estuaries to Hypoxia as a Prerequisite to Designing a Pertinent Monitoring Strategy of Dissolved Oxygen - Schmidt, Sabine; Diallo, Iris I.; Derriennic, Hervé; Fallou, Hélène; Lepage, Mario (Frontiers in Marine Science, 2019)
Globally, there has been a decrease in dissolved oxygen in the oceans, that is more pronounced in coastal waters, resulting in more frequent hypoxia exposure for many marine animals. Managing hypoxia requires an understanding of the dynamics of dissolved oxygen (DO) where it occurs. The French coast facing the Bay of Biscay (N-E Atlantic Ocean) hosts at least a dozen tidal and turbid estuaries, but only the large estuaries of the Gironde and the Loire, are subject to a continuous monitoring. Here, we compared the DO dynamics in these two systems, in order to evaluate to what extent it is possible to predict the sensitivity to hypoxia of a tidal and turbid estuary based on its most common and easily accessible characteristics (the estuary surface area and length, liquid and solid discharge, suspended particulate load, water renewal time, presence of cities). Whereas the hyperturbid Gironde estuary is the longest (170 km), implying longer water and particle residence times, and is bordered by a large metropole (> 750 000 inhabitants), only episodic summer hypoxia events (DO < 2 mg L-1) were recorded in its urban Garonne subestuary. In contrast, the turbid Loire estuary, smaller in terms of surface area and length, experiences permanent summer hypoxia. This demonstrates the inability to evaluate the susceptibility of a tidal and turbid estuary to hypoxia only by considering its general characteristics. We urge that there is a need for a pertinent DO survey strategy based on an initial assessment of DO in a specific estuary based on longitudinal investigations, in particular during the warm season (as higher water temperatures decrease DO solubility), for detecting the potential zones of minimum DO.